Catalyst free hydrazone ligation for protein labeling and modification using electron-deficient benzaldehyde reagents. Issue 38 (21st September 2018) - Xu, Yang; Wang, Yu; Liu, Peiyuan; Chu, Guo-Chao; Xu, Huajian; Li, Yi-Ming; Wang, Jun; Shi, Jing
Abstract : We developed a novel electron-deficient benzaldehyde reagent for catalyst free hydrazone ligation. Abstract : Bioorthogonal reactions have emerged as valuable tools for site-specific protein labeling and modification in vitro and in vivo . Hydrazone and oxime ligation has recently attracted considerable attention for wide applications in the conjugation of biomolecules. However, this kind of reaction has suffered from slow kinetics under physiological conditions and toxicity or complications of the reaction system due to catalysts. In this work we have developed an electron-deficient benzaldehyde reagent, which can be easily equipped with various types of bio-functional molecules for catalyst-free hydrazone ligation. The reagent can be equipped with not only small molecules such as fluorescence dyes or drugs, but also macromolecules like PEG. These can be precisely ligated to the C-terminus of proteins by an efficient hydrazone reaction at neutral pH and room temperature. The new reagent based catalyst-free hydrazone ligation provides a practical approach for the site specific modification of proteins.